2012
DOI: 10.1155/2012/910526
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Symmetric Lipomatosis: A Review of 3 Cases

Abstract: Multiple symmetrical lipomatosis, or Madelung's disease, is a rare disease of unknown etiology. It is characterized by the presence of loose adipose tissue deposits localized in the cervical region and in the upper body. The neoformations grow slowly and their initial consequence is purely esthetic. They can, however, lead to compression of the laryngotacheal area and of the esophagus. This disease usually affects middle-aged males from the Mediterranean area with a history of alcohol abuse. Although most case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…Furthermore, an association between metabolic disorders and alcoholism has been postulated [6,7,8]. Interestingly, it has been reported that chemotherapy and/or blood stem cell transplantation may be plausible causes of de novo multiple lipomatosis, possibly by stem cell mobilization following transplantation or chemotherapy [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an association between metabolic disorders and alcoholism has been postulated [6,7,8]. Interestingly, it has been reported that chemotherapy and/or blood stem cell transplantation may be plausible causes of de novo multiple lipomatosis, possibly by stem cell mobilization following transplantation or chemotherapy [9].…”
Section: Introductionmentioning
confidence: 99%
“…BSL typically affects middle-aged man of mediterranean origin with a history of alcohol abuse [5,6]. Although, some cases have also been reported in young adults, women and children, even without alcohol consumption reported, like as patient.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this disease is more common in the male gender (15:1 ratio), between 30 and 60 years old and in the Mediterranean population [3]. Chronic alcoholism history is present in 60-90% of the cases [2,6]. Madelung's disease phenotype may vary but most of the cases present with adipose tumefactions in the face, neck, occipital fossa and shoulder areas.…”
Section: Discussionmentioning
confidence: 99%
“…These complications are the main surgery indication in this disease [2]. Rarely, some patients present with malignant degeneration to liposarcomas and oropharyngeal tumors [8].…”
Section: Discussionmentioning
confidence: 99%